2017
DOI: 10.1007/s11696-017-0201-0
|View full text |Cite
|
Sign up to set email alerts
|

Manganese(II) complexes with Bn-tpen as powerful catalysts of cyclohexene oxidation

Abstract: Manganese(II) complex [(Bn-tpen)MnII]2+ activated dioxygen for oxidation of cyclohexene in acetonitrile (MeCN) and methanol (MeOH). In MeCN, ketone (2-cyclohexen-1-one), alcohol (2-cyclohexen-1-ol) and small amounts of epoxide (cyclohexene oxide) were produced in this reaction, while in MeOH only ketone was formed. In the most efficient experiment, the combination of 2.5 × 10−4 mol% [(Bn-tpen)MnII]2+ and 4 M cyclohexene under dioxygen atmosphere (p O2 = 1 atm) in MeCN after 24 h of reaction, gave the TON equal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…2b and c. The electron movement from the HOMO of spiro-OMeTAD to the Mn complex enhanced the production of hole carriers in spiro-OMeTAD, which improved the conductivity of spiro-OMeTAD. [46][47][48][49]…”
Section: Cyclic Voltammetrymentioning
confidence: 99%
“…2b and c. The electron movement from the HOMO of spiro-OMeTAD to the Mn complex enhanced the production of hole carriers in spiro-OMeTAD, which improved the conductivity of spiro-OMeTAD. [46][47][48][49]…”
Section: Cyclic Voltammetrymentioning
confidence: 99%
“…However, in acetonitrile, c-C 6 H 8 (O) is the dominant product for the investigated complexes. Furthermore, we have demonstrated the manganese(II) complex with the pentadentate ligand can activate dioxygen for the oxidation of cyclohexene [54].…”
Section: Introductionmentioning
confidence: 95%
“…Cyclohexene is a compound that is frequently exploited as a model substrate in preliminary catalytic studies. Due to the presence of single C-H and double C=C bonds susceptible to oxidation, studies on its reactivity serve as a good starting point for the discussion of the reaction mechanism and reactivity of this compound as well as other chemicals [54]. Previously, we found that in acetonitrile (MeCN) labile iron(II) complexes with 2,2'-bipyridine (bpy), [Fe II (bpy) 2 2+ ] MeCN activate dioxygen for the oxidation of cyclohexene [55], to ketone and alcohol.…”
Section: Introductionmentioning
confidence: 99%
“…25 °C) [ 81 ] [(Bn-TPEN)Mn II ] 2+ (1 mM)/Al(OTf) 3 (2 mM) /MeCN/CH 2 Cl 2 catalytic epoxidation of cyclooctene (0.05 M) corresponding oxide (89%), (temp. 0 °C, time: 3.5 h) [ 85 ] [(Bn-TPEN)Mn II ] 2+ (0.5–10 mM)/air or O 2 /MeCN and/or MeOH cyclohexene (1–4 M) oxidation corresponding ketone, alcohol, and epoxide; e.g cyclohexanone (12%), cyclohexenol (6%) and traces of epoxide **** [ 84 ] [(Bn-TPEN)Mn IV = O] 2+ (0.5–0.8 mM) /TFE/MeCN anthracene (0.10 mM), 9-methylanthracene (0.20 mM), 9,10-dimethylanthracene (0.25 mM) oxidation corresponding ketones – anthraquinones; e.g. anthracene was completely (100% yield) oxidized to anthraquinone (temp.…”
Section: N -Pentadentate Iron and Manganese Complexes – Recent Trends In Catalysismentioning
confidence: 99%
“…They also eliminate the need for more expensive and complex higher molecular weight porphyrin ligands [ 26 ]. [(Bn-TPEN)Mn] 2+ catalyze oxidation of cyclohexene by dioxygen to ketone and alcohol [ 84 ], and epoxidation of cyclooctene, where redox-inactive metal ions, acting as a Lewis acid in oxygen atom transfer reaction were used [ 85 ]. However, when there are no redox-inactive metal ions in the reaction medium, then the manganese(II) catalyst reacts very sluggish, (8.7% yield of epoxide), and addition of Al 3+ ions to manganese(II) complex significantly improves epoxidation (88.9% yield of epoxide) [ 85 ].…”
Section: N -Pentadentate Iron and Manganese Complexes – Recent Trends In Catalysismentioning
confidence: 99%